Off-court generic perceptual-cognitive training in elite volleyball athletes: Task-specific effects and levels of transfer - Fleddermann, M.-T.; Heppe, H.; Zentgraf, K. (Frontiers in Psychology, 2019)
Background: The nature of perceptual-cognitive expertise in interactive sports has gained more and more scientific interest over the last two decades. Research to understand how this expertise can be developed has not been addressed profoundly yet. In approaches to study this with interventional designs, only few studies have scrutinized several levels of transfer such as to the field. Therefore, the aim of this study was to examine the efficacy of a generic off-court perceptual-cognitive training in elite volleyball players on three different levels: task-specific, near-transfer, and far-transfer effects. Based on overlapping cognitive processes between training and testing, we hypothesized task-specific improvements as well as positive near- and far-transfer effects after a multiple-object tracking training intervention.